Political participation instruction for monk and novice students in Thailand - Hadpagdee, Saward; Choutikavatchagul, Songphon; Mason, Chairat; Aranyawat, Suttipun; Hngokchai, Phra Wasan; Singtong, Phramaha Komkai; Ruangsan, Niraj (Linguistics and Culture Review, 2021)
This research aimed (1) to study the political participation of the monk and novice students in MCUKK as the guideline to develop the political participation instruction for MCUKK students, (2) to suggest the ways to promote the political participation instruction of the monk and novice students. The population of the research was the bachelor degree students: monks and novices (n = 266) of MCUKK. The key informants (15) including 1 educational administrator, 2 directors of Political Science Programs (Bachelor and Master), and 2 lecturers, 10 students selected by Purposive Sampling. This study was conducted by means of the mixed research methodology: quantitative research and qualitative research. The tools used in this research were the five-rating scale questionnaire and an in-depth interview. The research findings indicated that (1) the political participation of the students in four studied aspects were statistically rated the moderate level; (2) the university lecturers should pay attention to educating the legal rights and importance of political participation in terms of voting, political news, political campaign and political rally for the students. The finding suggested that teaching political participation should be managed properly, although there is the law that prohibits monks or novices to get involved in politics.